ASSESSMENT OF CLUSTER POTENTIAL IN SLOVAKIA: CASE STUDY IN THE UPPER POVAŽIE REGION - Jozef Gáll; Anna Michálková (Zbornik Radova: Geografski institut "Jovan Cvijić", 2023)
As clusters currently represent a significant support in the development of regions, it is important to analyze their potential in the tourism industry. In Slovakia, tourism clusters work alongside local tourism organizations for legislative reasons. The main aim of the present study is to use appropriate identification methods to map the microeconomic environment of the selected tourism region and subsequent analysis to evaluate the existing preconditions for successful and efficient operation of the tourism cluster. The results of the survey serve as an input database for the application of the Principal Component Analysis (PCA) method, which revealed the current cluster potential in the Upper Považie region. The individual determinants of the Porter’s Diamond model achieved favorable results. Using multiple regression analysis, quantification and interpretation of the interrelationships between input variables were enabled. The applied analysis shows that the potential pillars for the creation of a tourism cluster in the Upper Považie region are the determinants of firm strategy, structure, and rivalry in the region, related and supporting industries, and factor conditions. The results show that the examined determinant factors create conditions for the functioning of a potential cluster in the region at an average level.